First report of Tunga trimamillata infection in a dog - Katherine M. Chaguay Villamar; Victoria M. Hernández Copello; Constanza Toro-Valdivieso; Belén M. Rivera Gomez-Barris (BMC Veterinary Research)
Abstract Background Tungiasis is a zoonotic parasitic disease caused by Tunga penetrans and, less commonly, Tunga trimamillata. It affects the skin of humans and animals in rural or low-income communities. The disease is considered endemic in Ecuador, with most cases reported in the Amazon and Andean regions. There are few cases reported on T. trimamillata in Ecuador, most of which have been reported in the canton of Santa Isabel, Azuay Province. Unlike T. penetrans, no cases of canine infection have been reported for T.trimamillata before. Case report A canine patient was presented for medical consultation with multiple white nodules in all four paws. Based on the anamnesis and clinical findings, tungiasis was established as the presumptive diagnosis. After careful removal and close inspection of the gravid female fleas, we noticed three protruding lobes in the anterior part of the neosome, a characteristic feature of the gravid T. trimamillata. After ten days of daily wound cleanings and antibiotics, the patient’s paws were fully healed. Conclusion To the best of our knowledge, we present the first case of T. trimamillata infection in dogs. This is also the first case of T. trimamillata detected in Guayaquil. However, the patient was imported from an area where T. trimamillata is considered endemic. Therefore, this report has further implications for the movement of domestic animals across the country and potential spread of parasites and other infectious agents from endemic to non-endemic areas.